THE SITE OF SANGIRAN AS A MEANS OF HISTORY-LEARNING: AN EFFORT TO INCREASE STUDENTS’ HISTORICAL AWARENESS - Warto; Tundjung Wahadi Sutirto; Rara Sugiarti (Naditira Widya, 2020)
History subject in secondary schools faces a number of challenges which may affect the efficiency of student learning outcomes. Several factors which influence such condition are the idea that history is less important than other subjects, lack of employing attractive educational methods and instruments, as well as limited facilities and learning resources in schools. An important aspect that needs to be reconsidered is the use of history-learning instrument beyond a classroom. This research explores the use of the archaeological site of Sangiran as a pre-literacy learning tool for junior high school students. This is a quantitative study which was carried out by a survey that involves the 10th grade high school students as research subjects. Sixty four students were divided into two groups, i.e. an experimental class consisting students who have visited the Sangiran site, and a control class of those who have not. The analysis indicates (sig 2 tailed) was 0.00 in the paired sample t test. Sig 0.00 is smaller than sig 0.05 (sig 2 tailed <sig 5-007). Thus, showing that the control class students did not share direct experience with historical material and passive learning activities. Consequently, they have not explored further the use of the Sangiran site as a means of learning. Students of the experimental class show better learning outcomes. The study concludes that learning history by visiting the Sangiran site can significantly increase awareness of the importance of history and encourage students' concern of the historical heritages. Mata pelajaran sejarah di sekolah menengah memiliki sejumlah tantangan yang dapat mempengaruhi efisiensi hasil belajar siswa. Beberapa faktor yang mempengaruhi kondisi ini, yaitu gagasan bahwa pendidikan sejarah kurang penting daripada mata pelajaran lain, kurangnya penerapan metode dan media pendidikan yang menarik, serta terbatasnya fasilitas dan sumber daya pembelajaran di sekolah. Aspek penting yang perlu dipertimbangkan kembali adalah penggunaan media pembelajaran sejarah di luar kelas. Penelitian ini mengeksplorasi penggunaan situs arkeologi Sangiran sebagai alat pembelajaran pra keaksaraan untuk siswa sekolah menengah pertama. Penelitian ini bersifat kuantitatif dengan menggunakan teknik survei yang melibatkan subjek penelitian siswa SMA kelas 10. Enam puluh empat siswa dibagi menjadi dua kelompok, yaitu kelas eksperimental yang terdiri dari siswa yang telah mengunjungi situs Sangiran, dan kelas kontrol dari mereka yang belum. Hasil analisis menunjukkan (sig 2 tailed) adalah 0,00 dalam t test sampel berpasangan. Sig 0,00 lebih kecil dari sig 0,05 (sig 2 tailed <sig 5-007). Dengan demikian diketahui bahwa siswa kelas kontrol tidak berbagi pengalaman langsung dengan materi sejarah dan kegiatan belajar pasif. Hal ini mengakibatkan mereka belum mengeksplorasi lebih lanjut penggunaan situs arkeologi Sangiran sebagai alat pembelajaran. Para siswa kelas eksperimental hasil belajarnya lebih baik. Penelitian ini menyimpulkan bahwa belajar sejarah dengan mengunjungi situs kuno Sangiran dapat secara signifikan meningkatkan kesadaran akan pentingnya sejarah dan mendorong perhatian siswa terhadap warisan sejarah.